Pengaruh Derajat Robekan Perineum Terhadap Skala Nyeri Perineum Pada Ibu Nifas Di Kabupaten Wonogiri - Triwik Sri Mulati; Dewi Susilowati (Poltekkes Kemenkes Surakarta, 2018)
Abstract: Perineal Laceration Level, Perineal Pain, Post Partum Mother. Some post partum mothers experienced the perineal laceration because of natural perineal laceration (rupture) or perineal episiotomy. Both of them would be able to cause perineal laceration from mild up to severe level. The level of perineal laceration would influence to perineal pain scale felt by post partum mother. The purpose of this research was to prove the influence of the perineal laceration level to the perineal pain scale on post partum mother. This research was analitical design. The data was analyzed using Paired-samples T-test. The respondents were 59 post partum mothers from Klaten District who experienced perineal laceration but without complication. The result showed the majority of perineal laceration level was 2ᵑᵈ level (89.8%) and the majority of perineal pain scale was mild pain (66.1%). Based on Paired-samples T-test account, the p value was 0.06, p > 0.05 so that it could be concluded that there was no influence of perineal laceration level to the perineal pain scale on post partum moher.